(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يسلط هذا البحث الضوء على أبرز أسس منهج سيبويه في كتابه, وهي في مجملها لا تختلف عن الأسس التي يستند إليها المنهج الوصفي الحديث, وقد اهتدى سيبويه في أوّل موسوعة لغويّة عربيّة, وبشكل ينمُّ على صواب منهجه وريادته في هذا المجال, ويتضح ذلك في المستويات اللّغويّة الثلاثة: الصّوتيّة والصّرفيّة والنّحْويّة. لقد تتبعنا الطريقة الّتي عالج بها الظواهر اللّغويّة, ومجموعة العمليات العقلية الاستدلاليّة الّتي استند إليها لكل جوانب هذه الظاهرة, إلى جانب الأسس الواقعيّة الّتي اعتمدها في تحقيق ذلك, وهي نفسها الّتي شاعت في الغرب فيمَ بعد, على النحو الآتي: ( السماع- اللّغة والكلام- اللّغة المنطوقة واللّغة المكتوبة- وحدة الزمان والمكان- الاستقراء- التصنيف) . This research highlights the most recognizable basics of Sibaweih’s methodology in his book. Altogether, they are not different from the modern descriptive approach. Sibaweih appears in the first Arabic Linguistics Encyclopaedia, in a way that presents the righteousness of his pioneering methodology, as is apparent in the three linguistic levels of: Phonology, Morphology and Syntax. We have traced the method he followed to treat the linguistic phenomena, which in all its forms constitute a constellation of semantic and intellectual operations based on all aspects of this phenomenon, next to the realistic principles that he relied on to achieve his goal. Themselves are the principles that gained circulation in the West later on; as follows: listening; language and speech; spoken and written language; unity of time and place; induction; and categorization.